Ag supported on carbon fiber cloth as the catalyst for hydrazine oxidation in alkaline medium. (20th December 2015) - Liu, Ran; Ye, Ke; Gao, Yinyi; Zhang, Wenping; Wang, Guiling; Cao, Dianxue
Highlights: CFC supported microspherical Ag is obtained by square-wave potential method. Ag/CFC electrode has high catalytic activity toward hydrazine oxidation. Hydrazine oxidation on the electrode proceeds by a near 4-electron pathway. Abstract: Silver particles with microspheric structure are directly electrodeposited on carbon fiber cloth (CFC) substrate by square-wave potential electrodeposition method. The electrocatalytic behaviors of the Ag/CFC electrode toward hydrazine oxidation in alkaline solution are examined by cyclic voltammetry and chronoamperometry. An onset oxidation potential of -0.5 V and a peak current density of 30 mA cm −2 are achieved in the solution containing 1.0 mol L −1 KOH and 20.0 mmol L −1 hydrazine. The microspheric structure of the Ag/CFC electrode provides large electroactive surface area, hence, abundant active sites are vacant for hydrazine oxidation. The calculated apparent activation energies at different potentials show that hydrazine electro-oxidation at higher potential has faster kinetics than that at lower potential. In addition, the transfer electron number of hydrazine oxidation reaction on the Ag/CFC electrode is close to four, suggesting hydrazine is almost completely electrooxidized on the electrode and the full use of hydrazine fuel is basically achieved.